KAJIAN PEMASOKAN-KEBUTUHAN ASPAL BUTON INDONESIA - Agus Miswanto; Ijang Suherman; Triswan Suseno; Willy Pravianto (Indonesian Mining Journal, 2023)
National asphalt that was needed around 1.2 million tons per year are fulfilled by Pertamina's oil asphalt production around 272,040 tons (22.27%).  Such a production is related to US$283.77 million, Indonesian natural asphalt (Asbuton) from Buton around 21,226 tons (1.74%) that is worth US$9.13 million. Its shortfall was met by the an import of 945,180 tons (77.39%) that is worth of US$473.77 million. The Asbuton resources are enormous around 792.5 million tons and its reserve is approximately 182.65 million tons. There are 16 Asbuton processing factories with the total capacity of roughly 2.03 million tons per year. However, their production is still 43,128 tons per year. It means the production utility is only 2.1% of the total production capacity. This study aims to optimize the use of Asbuton. Secondary data is obtained from various agencies, official websites, research reports, journals, and sharing sessions. Data analysis using an econometric model with a simple linear regression equation. The results show that the import substitution program starts in 2023, where the national asphalt needs are 935,180 tons, and its production is 253,473 tons and its import substitution in the first year is gradually around 96,061 tons, which means that the will be 585,647 tons so that the country can save foreign exchange of US $ 65.66 million. In 2031, substitution has exceeded the imports number, result and the excess capacity, thus opening up the export opportunities of 96,060 tons. Referring to such condition, the country can get additional income around US$656.59 million. This situation will continue until the end of the projection year in 2045.